Analisis Beban Kendaraan Terhadap Kerusakan Perkerasan Lentur (Aspal) Pada Ruas Jalan Raya Demak Jepara Km 37 – Km 39. - Adit, Prihardhita Cahya Finnahar; Adi Saputro, Yayan; Nor Hidayati (Jurnal Civil Engineering Study, 2025)
Demak - Jepara Highway is one of the roads that plays an important role as the main route for the mobility of people and goods in the northern coastal area of ​​Central Java. The research method in this analysis uses the Bina Marga method, Pavement Condition Index (PCI), and Surface Distress Index (SDI). After obtaining data related to vehicle load and flexible pavement damage, the data is then analyzed using the Bina Marga method, Pavement Condition Index (PCI), and Surface Distress Index (SDI). And also calculate the vehicle load to determine the effect of vehicle load on flexible pavement damage (asphalt). From the calculation of the Truck Factor value, the Truck Factor value is 1.995 1, where this value indicates damage caused by traffic load factors. Based on the results of the analysis of the type of damage using the Bina Marga method, the Road Condition Value on the Demak Jepara highway section Km 37 - Km 39 with a length of 2.1 km is 5. So it is included in the category of Good road conditions (B) or 6% with a routine Maintenance handling program. While the results of the calculation of the priority order on Jl. Raya Demak Jepara Km 37 - Km 39 are 6. which is included in the priority class category "B" or Periodic Maintenance. For the results of the analysis of the type of damage using the PCI method, the PCI value for the Demak Jepara highway section Km 37 - Km 39 is 43.904, so it can be concluded that the condition of the road pavement on the Demak Jepara highway section Km 37 - Km 39 is Fair (fair) with a road length of 2.1 km which is divided into 21 STA segments and is included in the Routine Maintenance type. Meanwhile, for the results of the analysis of the type of damage using the SDI method, the average value of SDI (Surface Distress Index) on the Demak Jepara highway Km 37 - Km 39 for all road segments was 30.47, which is included in the (Good) category with a routine maintenance program type. Damage handling measures are needed at the points where the damage occurs. In order to minimize accidents and provide a sense of security and comfort for road users. And to prevent the spread of damage even wider.